The impact of 14th Malaysian General Election on Bursa Malaysia by using a complex network approach - Bahaludin, Hafizah; Mahamood, Fatin Nur Amirah; Hasanuddin Amran, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
A complex system such as a financial market can be visualized in the form of a network. For instance, a network is used to exhibits the interconnection between stocks that are traded in the market. In addition, it shows many important embedded information in a network such as structural changes that are affected from any events. Even though, the applications of a complex network has been used to investigate the behaviour of Bursa Malaysia, far too little attention has been paid to the effect of political event towards Malaysian financial market. Thus, this study concentrates the effect of 14th Malaysian General Election towards Bursa Malaysia. The first objective is to construct a financial network of Bursa Malaysia and the second objective is to examine the importance of the stocks on the financial network. The data used are the shariah-compliant stocks listed on Shariah Advisory Council (SAC). The duration of the study is divided into two periods which are the six months before and after the general election. The minimal spanning tree is used to construct a network and centrality measures are used to examine the role of a stock in a network. The empirical findings revealed and shed light on the impact of the 14th Malaysian General Election on shariah-compliant securities.